Efficiency of 3D‐Ordered Macroporous La0.6Sr0.4Co0.2Fe0.8O3 as an Electrocatalyst for Aprotic Li‐O2 Batteries. Issue 2 (14th February 2019) - Cheng, Junfang; Jiang, Yuexing; Zou, Lu; Zhang, Ming; Zhang, Guozhu; Wang, Ziling; Huang, Yizhen; Chi, Bo; Pu, Jian; Jian, Li
Abstract: Li‐O2 batteries (LOBs) with an extremely high theoretical energy density have been reported to be the most promising candidates for future electric storage systems. Porous catalysts can be beneficial for LOBs. Herein, 3D‐ordered macroporous La0.6 Sr0.4 Co0.2 Fe0.8 O3 perovskite oxides (3D‐LSCF) are applied as cathode catalysts in LOBs. With a high Brunauer‐Emmett‐Teller surface area (21.8 m 2 g −1 ) and unique honeycomb‐like macroporous structure, the 3D‐LSCF catalysts possess a much higher efficiency than La0.6 Sr0.4 Co0.2 Fe0.8 O3 (LSCF) nanoparticles. The unique 3D‐ordered macropores play a significant role in the product deposition as well as oxygen and electrolyte transmission, which are crucial for the discharge‐charge processes of LOBs. Abstract : Power dimension : Three‐dimensionally ordered macroporous La0.6 Sr0.4 Co0.2 Fe0.8 O3 perovskite oxides (3D‐LSCF) are applied as cathode catalysts in Li‐O2 batteries (LOBs). With a high Brunauer‐Emmett‐Teller surface area (21.8 m 2 g −1 ) and unique honeycomb‐like macroporous structure, the 3D‐LSCF catalysts possess a much higher efficiency than La0.6 Sr0.4 Co0.2 Fe0.8 O3 nanoparticles. The unique 3D‐ordered macropores play a significant role in the product deposition as well as oxygen and electrolyte transmission, which are crucial for the discharge‐charge processes of LOBs.